Primary B-cell non-Hodgkin lymphoma of the parotid gland: An analysis based on the SEER database. Issue 17 (28th April 2023) - Chen, Xiang-Lei; Zhao, Lu-Ming; Cai, Yuan-Hua; Li, Jing-Gang; Li, Xin
Abstract : Primary malignant lymphoma of the parotid gland is a rare entity. The disease is often misdiagnosed, and its survival factors remain unclear. This study included patients diagnosed with primary B-cell non-Hodgkin lymphoma of the parotid gland from 1987 to 2016 in the surveillance, epidemiology, and end results program. Univariate survival analysis was conducted using the Kaplan–Meier method, and multivariate analysis was performed using the Cox proportional hazards regression model. A competing risks regression model was applied to estimate the specific risks associated with parotid lymphoma mortality. A total of 1443 patients were identified. The overall survival of indolent primary B-cell lymphoma of the parotid gland was higher than that of aggressive lymphoma (hazard ratio 0.53, 95% confidence interval 0.44–0.64, P  < .001), and older patients (≥70 years) exhibited inferior overall survival. Histological subtype and age are important prognostic factors in patients with primary B-cell non-Hodgkin lymphoma of the parotid gland.